ESTHER’S PSYCHOPATHY IN DAVID LESLIE JOHNSON’S ORPHAN MOVIE SCRIPT - Pujimahanani, Cahyaningsih; Aningsih, Sri Dwi (Dinamika : Jurnal Sastra dan Budaya, 2016)
Psychopathy is one of the dangerous mental disorder. The thesis writer focuses her thesis on the analysis of psychopathy in literary work, movie script written by David Leslie Johnson entitled Orphan in 2009.The thesis writer focuses her analysis on the proofs of Esther’s psychopathy in David Leslie Johnson’s Orphan movie script, the causes of Esther’s psychopathy in David Leslie Johnson Orphan movie script , and the effects of Esther’s psychopathy in David Leslie Johnson’s Orphan movie script on herself, Max, and Kate. The objectives of the study is; to find out the  proofs of Esther’s psychopathy in David Leslie Johnson’s Orphan movie script, to find out the causes of Esther’s psychopathy in David Leslie Johnson’s Orphan movie script, and to find out the effects of Esther’s psychopathy in David Leslie Johnson’s Orphan movie script. The thesis writer also applies qualitative research as well. The result of this study is there are four proofs of Esther’s psychopathy in David Leslie Johnson’s Orphan movie script, they are; Pathiological lying, Lack of remorse and guilt, lack of empathy, and manipulative. The thesis writer also analysis the causes of Esther’s psychopathy in David Leslie Johnson’s Orphan move script. There are three causes of Esther’s psychopathy, they are; physical abuse, sexual abuse, and emotional or psychological abuse. In addition, the effects of Esther’s psychopathy. They are; on herself, Max, and Kate.  Keyword: Psychopathy, child abuse, crime